Геоморфологія палеолітичних пам’яток долини річки Бакшали - Березницька, І.М. (Археологія, 2003)
У статті розглянуто геоморфологічну ситуацію в долині р. Бакшала в період проживання там великої групи пізньопалеолітичного населення (25 місцезнаходжень), а також проаналізовано джерела сировини. Эта статья нацелена на анализ геоморфологической ситуации долины речки Бакшала на правом берегу залива Южного Буга. В южной части Бакшалинской долины известно 25 палеолитических памятников и четыре из них исследованы. Показаны природные условия экономического развития жителей микрорегиона в позднем палеолите. Особенности рельефа Бакшалинской лолины способствовали проживанию бизонов и других животных. Охарактеризованы направления охоты с использованием геоморфологии правого и левого берегов, источники сырья для изготовления орудий, направления поисков и сбора камня древними людьми. This article is aimed to analyze the géomorphologie situation of the Bakshala river valley in the right bank of South Bug inflow. There are 25 paleolithic sites in the southern part of the Bakshala valley and four of them have been investigated. Nature conditions of economical development of micro-region inhabitants in the late Palaeolit have been shown. The relief features of the Bakshala valley was conductive to living bison and other animals. The direction of hunting with using geomorphology of right and left banks, the raw materials sources for implement preparation, the directions of searching and collecting the stone materials by ancient people were characterized.